Therapeutic hypothermia in patients with out-of-hospital arrest. Issue 16 (2nd May 2015) - Maznyczka, Annette M; Gershlick, Anthony H
Abstract : Therapeutic hypothermia (TH) is increasingly used in patients presenting with out-of-hospital cardiac arrest (OHCA). Such strategies derive from data that suggest TH may improve survival and attenuate adverse neurological outcomes associated with the cardiac arrest. Consequently, TH has been integrated into various guidelines for the management of OHCA and has become a focussed strategy, particularly in patients with ST-segment elevation myocardial infarction. However, there remains uncertainty over the true impact of TH. In patients with OHCA due to asystole or pulseless electrical activity, overall available evidence suggests that TH does not improve neurological outcomes and survival. While in patients with OHCA due to ventricular fibrillation or ventricular tachycardia, observational studies and small, randomised studies have suggested there may be survival benefits and improved neurological recovery. However, even here, trial data robustness has been questioned, with ongoing debate regarding the optimum temperature for managing patients with OHCA and optimal timing of its initiation. More uniform and robust guidelines for the application of TH for patients with OHCA are required, but can only be formulated on appropriately sized robust trials. This review examines the current status of TH.